High cross-linking low-friction gel polymer electrolyte, preparation method and lithium battery

CN122677528BActive Publication Date: 2026-10-27CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611184474.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

尽管相关研究已取得一定进展,但受限于聚合物骨架的柔性线性分子链结构以及醚氧基团对锂离子的强配位作用,锂离子被牢牢地束缚在聚合物骨架周围,离子迁移行为呈现出高摩擦特性,不利于电池的功率密度和低温性能

Benefits of technology

[0017]本发明具有的有益效果是:提供了兼具高离子电导率、宽电化学稳定窗口及高安全性的高交联低摩擦凝胶聚合物电解质,解决了现有聚合物电解质因柔性线性链段、醚氧基团作用所导致的锂离子高摩擦传输及抗氧化稳定性不足等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677528B_ABST
    Figure CN122677528B_ABST
Patent Text Reader

Abstract

The application provides a high-crosslinking low-friction gel polymer electrolyte, a preparation method and a lithium battery, the electrolyte comprising a three-dimensional network framework formed by polymerization of a double-bond-containing fluorinated cyclotriphosphazene crosslinking agent and a fluorinated acrylic ester monomer, and a base electrolyte solution; wherein the double-bond-containing fluorinated cyclotriphosphazene crosslinking agent accounts for 0.5wt% to 20wt% of the mass of the electrolyte, the fluorinated acrylic ester monomer accounts for 0.5wt% to 30wt% of the mass of the electrolyte, and the concentration of lithium salt in the base electrolyte solution is 0.5mol / L to 5mol / L. The application provides an in-situ solidified gel polymer electrolyte with high ionic conductivity, a wide electrochemical stability window and high safety, and effectively solves the problems of slow ion transmission kinetics and insufficient interface stability of existing polymer electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a highly cross-linked, low-friction gel polymer electrolyte, its preparation method, and a lithium battery. Background Technology

[0002] Lithium-ion batteries, as a type of highly efficient energy storage and conversion device, have expanded widely from portable electronic devices to emerging application scenarios such as drones, new energy vehicles, and energy storage power stations due to their numerous advantages, including high output voltage, high energy density, long cycle life, and no memory effect. However, limited by the traditional transition metal oxide cathode and graphite anode systems based on intercalation chemistry mechanisms, the energy density of current commercial lithium-ion batteries is gradually approaching the theoretical limit of 300 Wh / kg. Meanwhile, the organic liquid electrolytes used in these batteries, due to their flammable and volatile properties, are highly susceptible to severe thermal runaway and combustion risks under thermal, mechanical, or electrochemical abuse conditions, posing a significant safety hazard.

[0003] To simultaneously achieve further improvements in energy density and ensure intrinsic battery safety, solid-state battery technology, which couples lithium metal anodes with solid-state electrolytes, is widely regarded as a next-generation battery solution with great potential. Among various solid-state electrolyte systems, polymer electrolytes exhibit particularly outstanding application prospects due to their low mass density, good mechanical toughness, abundant synthesis strategies, lower manufacturing costs, and good compatibility with existing large-scale production processes.

[0004] Currently, most polymer electrolyte systems are constructed based on unsaturated monomers containing ether oxygen groups, such as polyethylene glycol acrylate monomers or cyclic ether monomers that can undergo ring-opening polymerization. Although some progress has been made in related research, the flexible linear molecular chain structure of the polymer backbone and the strong coordination effect of the ether oxygen groups on lithium ions limit the lithium ions to be firmly bound around the polymer backbone. The ion migration behavior exhibits high frictional characteristics, which is detrimental to the power density and low-temperature performance of the battery.

[0005] Furthermore, the ether radical group exhibits poor antioxidant stability, with its electrochemical stability window typically below 4.0V (vs. Li). + The polymer electrolyte ( / Li) is difficult to match the operating voltage requirements of high-nickel layered oxide cathode materials (such as NCM811 and NCM955). Under high voltage, the polymer electrolyte is prone to continuous oxidative decomposition, generating a large number of low molecular weight organic fragments. This not only degrades the structural density and mechanical strength of the solid electrolyte interface layer, but also destroys its electrochemical stability, ultimately leading to a sharp decline in battery cycle life. Summary of the Invention

[0006] The purpose of this invention is to provide a highly cross-linked, low-friction gel polymer electrolyte, its preparation method, and a lithium battery to solve the problems mentioned in the background art.

[0007] The technical solution adopted in this invention is: a highly cross-linked, low-friction gel polymer electrolyte, comprising: a three-dimensional network skeleton formed by polymerization of a fluorinated cyclotriphosphazene cross-linking agent containing double bonds and a fluorinated acrylate monomer, and a basic electrolyte; wherein: the fluorinated cyclotriphosphazene cross-linking agent containing double bonds accounts for 0.5wt%~20wt% of the mass of the electrolyte, the fluorinated acrylate monomer accounts for 0.5wt%~30wt% of the mass of the electrolyte, and the concentration of lithium salt in the basic electrolyte is 0.5mol / L~5mol / L.

[0008] Preferably, the fluorinated cyclotriphosphazene crosslinking agent containing double bonds includes any one or more of fluorinated acrylate-cyclotriphosphazene and fluorinated methacrylate-cyclotriphosphazene.

[0009] Preferably, the fluorinated acrylate monomer includes one or more of 2,2,2-trifluoroethyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecylfluoroheptyl acrylate, and 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate.

[0010] Preferably, the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, and lithium difluorooxalate borate.

[0011] Preferably, the base electrolyte contains a non-aqueous solvent, which includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether.

[0012] Preferably, the base electrolyte contains a diluent, which includes one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,1,3,3-pentafluorobutane.

[0013] The technical solution of the present invention also includes: a method for preparing the above-mentioned highly cross-linked low-friction gel polymer electrolyte, which includes the steps of: mixing a fluorinated cyclotriphosphazene cross-linking agent containing double bonds, a fluorinated acrylate monomer, a basic electrolyte and an initiator in a preset ratio, and carrying out a polymerization reaction at a preset temperature to obtain a highly cross-linked low-friction gel polymer electrolyte.

[0014] Preferably, the polymerization reaction is carried out at a temperature of 35~70℃ for 0.5h~12h.

[0015] Preferably, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.

[0016] The technical solution of the present invention also includes: a lithium battery, wherein the lithium battery contains the above-mentioned highly cross-linked low-friction gel polymer electrolyte.

[0017] The beneficial effects of this invention are: it provides a highly cross-linked, low-friction gel polymer electrolyte that combines high ionic conductivity, a wide electrochemical stability window, and high safety, and solves the problems of insufficient lithium-ion high-friction transport and antioxidant stability caused by the flexible linear segments and ether oxygen groups in existing polymer electrolytes. Attached Figure Description

[0018] Figure 1 This is a scanning electron microscope image of the three-dimensional network framework in the highly cross-linked, low-friction gel polymer electrolyte prepared in Example 1 of the present invention;

[0019] Figure 2 These are the thermogravimetric curves of the electrolytes or electrolyte solutions prepared in Embodiment 1 and Comparative Examples 1-2 of this invention at 60°C.

[0020] Figure 3 The electrolytes or electrolyte solutions prepared in Examples 1, 1, and 3 of this invention are... 7 Li NMR spectrum;

[0021] Figure 4 This is a graph showing the test results of lithium-ion relaxation rates of the electrolytes or electrolyte solutions prepared in Examples 1-3, Comparative Example 1, and Comparative Example 3-5 of the present invention.

[0022] Figure 5 These are the ionic conductivity-temperature curves of the electrolytes or electrolyte solutions prepared in Examples 1, 1, and 3 of this invention.

[0023] Figure 6 This is a graph showing the lithium-ion transport number test results of the electrolytes or electrolyte solutions prepared in Examples 1-3, Comparative Example 1, and Comparative Examples 3-5 of the present invention;

[0024] Figure 7 Long-cycle performance curves of lithium metal pouch batteries assembled using the electrolyte prepared in Example 1 of this invention. Detailed Implementation

[0025] To better illustrate the objectives, complete technical approach, and advantages of this invention, the following detailed description will be provided in conjunction with specific embodiments. However, the embodiments described below are only a part of the embodiments of this invention and do not include all embodiments. Other embodiments that can be obtained by those skilled in the art without creative effort based on the embodiments of this invention are all within the protection scope of this invention.

[0026] In the embodiments described below, unless otherwise specified, the conventional methods used are all technical means recognized or commonly used by those skilled in the art, and the instruments, reagents, consumables, etc. used in the embodiments of the present invention can be obtained through legitimate commercial channels.

[0027] This invention provides a highly cross-linked, low-friction gel polymer electrolyte, which includes a three-dimensional network framework formed by polymerizing a fluorinated cyclotriphosphazene cross-linking agent containing double bonds and a fluorinated acrylate monomer, and a basic electrolyte composed of a lithium salt, a non-aqueous solvent, and a diluent.

[0028] The above-mentioned highly cross-linked, low-friction gel polymer electrolyte was prepared using the following method steps:

[0029] S1. Fluorinated cyclotriphosphazene crosslinking agent containing double bonds, fluorinated acrylate monomer, basic electrolyte and initiator are mixed in a preset ratio to prepare a precursor solution.

[0030] S2. The precursor solution is placed at a preset temperature to carry out a polymerization reaction to obtain a highly cross-linked, low-friction gel polymer electrolyte.

[0031] Based on the above preparation method, a fluorinated cyclotriphosphazene crosslinking agent containing double bonds undergoes crosslinking polymerization with a fluorinated acrylate monomer under the action of an initiator to form a three-dimensional network framework. On the one hand, the fluorinated cyclotriphosphazene crosslinking agent containing double bonds, as a multifunctional topological crosslinking agent, can significantly increase the crosslinking density of the system and endow the three-dimensional network framework with a rich porous structure, enabling the three-dimensional network framework to effectively contain and seal the basic electrolyte, reducing the risk of liquid evaporation and leakage. At the same time, the cyclotriphosphazene group has excellent phosphorus-nitrogen synergistic flame retardant properties, which can scavenge hydrogen free radicals in the chain combustion reaction process, thereby blocking the gas phase combustion process. In addition, a carbonized layer is generated on the surface of the three-dimensional network framework under high temperature conditions, covering the electrolyte surface, inhibiting the release of flammable gases and isolating the air supply. The above multiple mechanisms work synergistically, enabling the electrolyte to play a role in both physical sealing and chemical flame retardancy, jointly improving the intrinsic safety of the battery.

[0032] On the other hand, compared with the ether oxygen segments in the existing electrolyte system which have strong lithium-ion coordination ability, the coupling between the fluorinated segments in the above-mentioned three-dimensional network framework and lithium ions is weaker, exhibiting low polarity and lithium salt phobicity. Lithium ions are more likely to maintain the original solvation structure dominated by ion pairs, and the migration process is basically not hindered by the three-dimensional network framework, exhibiting low frictional conduction characteristics, which is beneficial to improving the power density and low temperature performance of the battery.

[0033] Furthermore, the fluorinated segments in this three-dimensional network framework exhibit superior antioxidant stability compared to conventional ether oxygen segments, resulting in excellent high-voltage stability of the electrolyte, with an oxidation stability potential exceeding 5V (vs. Li). + This electrolyte (Li-based) can match the operating voltage requirements of high-nickel layered oxide cathode materials. During battery operation, it forms a bilayer interface layer near the electrodes: a near-electrode layer rich in lithium fluoride inorganic matter and a near-electrolyte layer rich in fluorinated polymers. The near-electrode layer has a high Young's modulus, thus providing sufficient mechanical strength to suppress lithium dendrite growth, while the near-electrolyte layer exhibits hydrophobic properties, mitigating the chemical corrosion of the electrodes by the base electrolyte. These multiple mechanisms work synergistically to maintain excellent interfacial stability between the electrolyte, the lithium anode, and the high-voltage cathode, significantly improving the cycle life and wide-temperature tolerance of ampere-hour-class lithium batteries.

[0034] Based on the aforementioned technical approach and considering the actual preparation process, research has shown that selecting the following raw material components within the specified ranges can yield a highly cross-linked, low-friction gel polymer electrolyte with superior overall performance. Specifically:

[0035] Considering that different fluorinated cyclotriphosphazene crosslinking agents containing double bonds exhibit different crosslinking polymerization activities due to differences in their structure and properties, this invention preferably uses fluorinated acrylate-cyclotriphosphazene or fluorinated methacrylate-cyclotriphosphazene as the fluorinated cyclotriphosphazene crosslinking agent component containing double bonds. The fluorinated acrylate group (or fluorinated methacrylate group) includes an acryloyloxy group (or a methacryloyloxy group) and a fluorinated alkoxy group. The oxygen atom in the acryloyloxy group (or the methacryloyloxy group) is bonded to the carbon atom in the fluorinated alkoxy group, and the other end of the fluorinated alkoxy group is covalently bonded to the phosphorus atom in the cyclotriphosphazene group via its own oxygen atom. The number of carbon atoms and fluorine atoms in the aforementioned fluorinated alkoxy group can be selected according to actual needs, and this invention does not limit this selection.

[0036] In some embodiments of the present invention, the fluorinated cyclotriphosphazene crosslinking agent containing double bonds is as shown in the following structural formula 1 or structural formula 2.

[0037]

[0038] Based on the weak coupling between fluorinated segments and lithium ions and their multiple functional properties, and considering that the higher the degree of fluorine substitution, the more significant the aforementioned performance gains become, this invention preferably uses 2,2,2-trifluoroethyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecylfluoroheptyl acrylate, or 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate as the fluorinated acrylate monomer.

[0039] The initiator can be any one or more of azo initiators or peroxide initiators, preferably azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, etc. The present invention does not make any particular limitation, as long as it can effectively initiate the cross-linking polymerization between the aforementioned monomers containing double bonds.

[0040] The lithium salt is preferably one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, and lithium difluorooxalate borate.

[0041] The non-aqueous solvent can be any one or more of ester solvents or ether solvents, preferably dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, etc.

[0042] The specific type and amount of diluent can be selected and adjusted within a conventional range. Its main function is to dilute the high-concentration system composed of non-aqueous solvents and lithium salts, thereby forming a locally high-concentration electrolyte system. This not only reduces the overall viscosity and cost of the electrolyte by introducing a large amount of inert solvent, but also maintains the solvation structure dominated by ion-pair aggregates, providing a basis for the formation of a stable solid electrolyte interface layer on the lithium metal surface. In addition, based on considerations of the intrinsic safety of the battery, a fluorinated diluent is preferred to form a synergistic effect with the fluorinated segments in the three-dimensional network framework. At the same time, the porous confined structure of this three-dimensional network framework can serve as a storage and slow-release carrier for the diluent, enabling continuous and controllable release of the diluent. When heated, both release fluorine free radicals, blocking the gas-phase combustion process. Alternatively, the fluorinated diluent may be any one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,1,3,3-pentafluorobutane.

[0043] To achieve the construction of the aforementioned locally high-concentration electrolyte system, the introduction of a diluent is crucial. However, research has shown that a post-mixing process involving direct compounding of the base electrolyte with a double-bonded fluorinated triphosphazene crosslinking agent, fluorinated acrylate monomer, and initiator is insufficient to achieve the desired polymerization conversion rate. To overcome this technical bottleneck, this invention optimizes the preparation method of the aforementioned precursor solution to include the following steps:

[0044] S11. Add the lithium salt and initiator to a non-aqueous solvent and stir at room temperature until completely dissolved;

[0045] S12. Add a fluorinated cyclotriphosphazene crosslinking agent containing double bonds and a fluorinated acrylate monomer to the mixture obtained in step S11, and stir at room temperature until the mixture is homogeneous.

[0046] S13. Add a diluent to the mixture obtained in step S12 and stir at room temperature until a clear and transparent precursor solution is formed.

[0047] Through systematic optimization of the relative contents of the above-mentioned components and comprehensive evaluation of key properties such as ionic conductivity, electrochemical stability window, and mechanical strength, this invention further explores and determines the preferred ratio range of each component in the highly crosslinked, low-friction gel polymer electrolyte. Specifically, the double-bonded fluorinated triphosphazene crosslinking agent accounts for 0.5wt% to 20wt% of the electrolyte mass, the fluorinated acrylate monomer accounts for 0.5wt% to 30wt% of the electrolyte mass, the initiator accounts for 0.05wt% to 2wt% of the electrolyte mass, and the balance is the basic electrolyte, in which the concentration of lithium salt is 0.5mol / L to 5mol / L.

[0048] To ensure sufficient reaction of all components and obtain a product with excellent overall performance, the polymerization temperature in step S2 is controlled within the range of 35~70℃, and the reaction time can be adaptively adjusted between 0.5h and 12h depending on the type of initiator selected and the target conversion rate. Under these conditions, the conversion rate of unsaturated double bonds can reach over 97%, and the amount of unreacted monomer residue is at a low level, effectively avoiding the adverse effects of residual monomers on battery interface stability and cycle life.

[0049] Another aspect of the present invention provides a lithium battery containing the above-mentioned highly cross-linked, low-friction gel polymer electrolyte, which is formed by in-situ polymerization using the above-mentioned preparation method. That is, after the positive electrode, negative electrode and separator are assembled, the precursor solution is injected into the battery. After standing to allow the positive electrode and negative electrode to be fully wetted, the temperature is raised to carry out the polymerization reaction, and the above-mentioned electrolyte is generated in situ.

[0050] The aforementioned lithium batteries include lithium-ion batteries or lithium metal batteries, and their battery form is not limited, including any one of cylindrical batteries, pouch batteries, or prismatic batteries.

[0051] The cathode material in a lithium battery includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, and ternary cathode materials, preferably a ternary cathode material. For example, the ternary cathode material is LiNi. x Co y Mn 1-x-y O2, where 0 < x < 1, 0 < y < 1, and x + y < 1.

[0052] The negative electrode material in a lithium battery includes one or more of lithium metal, graphite, silicon, and silicon-carbon composite materials, with lithium metal being the preferred material.

[0053] The separator in a lithium battery includes one or more of the following: polyolefin separators, polyimide separators, polyvinylidene fluoride separators, glass fiber separators, and ceramic separators, preferably polyolefin separators. The separator is placed between the positive and negative electrodes during battery assembly.

[0054] Based on the above technical solution, the present invention solves the problems of high frictional transport of lithium ions and insufficient antioxidant stability caused by the flexible linear segments and ether oxygen groups in existing polymer electrolytes. At the same time, it also takes into account the defect of poor controllability of reaction process in the large-scale preparation of electrolytes, and obtains a highly cross-linked low frictional gel polymer electrolyte with high ionic conductivity, wide electrochemical stability window and high safety.

[0055] Verification has shown that the electrolyte provided by this invention has a room temperature ionic conductivity exceeding 2 mS / cm and a lithium-ion transference number exceeding 0.6. Lithium batteries using this electrolyte exhibit excellent wide-temperature adaptability, operating stably within a temperature range of -30 to 90°C. Furthermore, given the significant advantages of this electrolyte in terms of ionic conductivity, lithium-ion transference number, and stability, it can reduce the amount of electrolyte used compared to existing technologies while maintaining the battery's electrochemical output capability. This allows lithium metal pouch batteries to break through the 600 Wh / kg energy density bottleneck under low N / P ratio and low E / C ratio conditions. Moreover, this battery system also possesses good safety characteristics, with a significantly lower maximum temperature rise during thermal runaway compared to existing commercial electrolyte systems.

[0056] The preparation process of the above electrolyte is simple, the raw material cost is low, and it has good prospects for industrial production. It is suitable for the field of high energy density and high safety lithium batteries.

[0057] The present invention will be further illustrated below through specific embodiments and comparative examples. The preparation of the electrolyte and the assembly of the battery are both carried out in a glove box filled with high-purity argon gas (purity ≥99.99%), and the water and oxygen content in the glove box is controlled below 0.01 ppm.

[0058] Example 1

[0059] Acrylic acid and 2,2,3,3-tetrafluoro-1,4-butanediol were dissolved in dichloromethane, and 4-dimethylaminopyridine was added as a catalyst. The mixture was reacted at room temperature under a nitrogen atmosphere. The intermediate product, 4-hydroxy-3,3,4,4-tetrafluorobutyl acrylate, was obtained by chromatographic purification. The obtained intermediate product was mixed with sodium hydride in tetrahydrofuran, and hexachlorocyclotriphosphazene was added dropwise at 0°C. After the addition was complete, the mixture was raised to room temperature for further reaction. After the reaction was completed, the mixture was filtered and washed multiple times to obtain the fluorinated acrylate-cyclotriphosphazene crosslinking agent (a slightly yellow liquid) shown in structural formula 1.

[0060] 1.01 g of lithium difluorosulfonylimide, 0.41 g of lithium hexafluorophosphate and 0.008 g of azobisisobutyronitrile were added to 0.90 mL of fluoroethylene carbonate and 1.80 mL of methyl ethyl carbonate, and stirred at room temperature until completely dissolved.

[0061] Add 0.15 g of the fluorinated acrylate-cyclotriphosphazene crosslinking agent (Structure 1) and 0.15 g of 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate to the above-obtained mixture, and stir at room temperature for 10 min until the mixture is homogeneous.

[0062] Add 2.70 mL of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to the mixture obtained above, and stir at room temperature for more than 30 min until a clear and transparent precursor solution is formed.

[0063] The precursor solution was transferred to an oven at 70°C and heated for 30 minutes to carry out the polymerization reaction, thereby obtaining the highly cross-linked, low-friction gel polymer electrolyte CPE-F.

[0064] Example 2

[0065] Compared with Example 1, the only difference is that the amount of 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate added in Example 2 is 0.30g.

[0066] Example 3

[0067] Compared with Example 1, the only difference is that the amount of 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate added in Example 3 is 0.45g.

[0068] Comparative Example 1

[0069] 1.01 g of lithium bis(trifluoromethanesulfonyl)imide and 0.41 g of lithium hexafluorophosphate were added to 0.90 mL of fluoroethylene carbonate and 1.80 mL of methyl ethyl carbonate, and stirred at room temperature until completely dissolved.

[0070] Add 2.70 mL of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to the above-obtained mixture, and stir at room temperature for more than 30 min until a clear and transparent solution is formed, thus obtaining electrolyte LE.

[0071] Comparative Example 2

[0072] 1.01 g of lithium bis(trifluoromethanesulfonyl)imide, 0.41 g of lithium hexafluorophosphate and 0.008 g of azobisisobutyronitrile were added to 0.90 mL of fluoroethylene carbonate and 1.80 mL of methyl ethyl carbonate, and stirred at room temperature until completely dissolved.

[0073] Add 0.1g of methyl acrylate to the mixture obtained above and stir at room temperature until the mixture is homogeneous.

[0074] Add 2.70 mL of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to the mixture obtained above, and stir at room temperature for more than 30 min until a clear and transparent precursor solution is formed.

[0075] The precursor solution was transferred to an oven at 70°C and heated for 30 minutes to carry out the polymerization reaction, thereby obtaining the linear gel polymer electrolyte LPE.

[0076] Comparative Example 3

[0077] 1.01 g of lithium bis(trifluoromethanesulfonyl)imide, 0.41 g of lithium hexafluorophosphate and 0.008 g of azobisisobutyronitrile were added to 0.90 mL of fluoroethylene carbonate and 1.80 mL of methyl ethyl carbonate, and stirred at room temperature until completely dissolved.

[0078] Add 0.15g of pentaerythritol tetraacrylate and 0.15g of tri(ethylene glycol) diacrylate to the mixture obtained above, and stir at room temperature until the mixture is homogeneous.

[0079] Add 2.70 mL of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to the mixture obtained above, and stir at room temperature for more than 30 min until a clear and transparent precursor solution is formed.

[0080] The precursor solution was transferred to an oven at 70°C and heated for 30 minutes to carry out the polymerization reaction, thereby obtaining the highly cross-linked, high-friction gel polymer electrolyte CPE-O.

[0081] Comparative Example 4

[0082] Compared with Comparative Example 3, the only difference is that the amount of tri(ethylene glycol) diacrylate added in Comparative Example 4 is 0.30g.

[0083] Comparative Example 5

[0084] Compared with Comparative Example 3, the only difference is that the amount of tri(ethylene glycol) diacrylate added in Comparative Example 5 is 0.45g.

[0085] Characterization and Testing

[0086] (1) The highly cross-linked, low-friction gel polymer electrolyte CPE-F prepared in Example 1 of this invention was washed and dried to obtain the insoluble component—the three-dimensional network framework. Its microstructure was characterized by scanning electron microscopy, and the characterization results are as follows: Figure 1 As shown.

[0087] Depend on Figure 1 It can be seen that the polymer skeleton formed by the fluorinated acrylate-cyclotriphosphazene crosslinking agent shown in structural formula 1 and the 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate monomer exhibits a complex three-dimensional crosslinking network structure. This three-dimensional porous structure can effectively accommodate and seal liquid components, inhibit the volatilization and leakage of the basic electrolyte, and maintain the stable physical form of the gel electrolyte.

[0088] (2) The electrolytes or electrolyte solutions prepared in Examples 1, 1, and 2 of this invention were placed in a forced-air drying oven at 60°C, and the changes in sample mass with heating time were recorded to characterize the thermal stability of the samples. The test results are as follows: Figure 2 As shown.

[0089] Depend on Figure 2 It can be seen that the electrolyte prepared in Comparative Example 1 exhibited the fastest rate of mass loss, decreasing to 62.8% of its initial mass after heating for 120 min and further decreasing to 48.6% after heating for 210 min. This indicates that the electrolyte exhibits severe volatilization under high-temperature conditions, exposing safety risks such as sealing failure and electrolyte leakage. The electrolyte prepared in Comparative Example 2 showed a slightly slower rate of mass loss, maintaining 60.8% of its initial mass after heating for 210 min. In contrast, the electrolyte prepared in Example 1 demonstrated excellent ability to retain liquid components, with a significantly slower mass loss trend, retaining 83.3% of its initial mass after heating for 210 min. These results indicate that a highly cross-linked polymer network can effectively suppress the escape of volatile components from the electrolyte, significantly improving the thermal stability of gel polymer electrolytes under high-temperature conditions, and is particularly suitable for locally high-concentration electrolyte systems containing highly volatile fluoroether diluents.

[0090] (3) Using liquid nuclear magnetic resonance 7 Lithium ion chemical environment in the electrolytes or electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 3 of this invention was detected by Li spectroscopy, and the detection results are as follows: Figure 3 As shown.

[0091] Using liquid-solid dual-purpose nuclear magnetic resonance7 Lithium ion relaxation rates in the electrolytes or electrolyte solutions prepared in Examples 1-3, Comparative Examples 1, and Comparative Examples 3-5 of this invention were detected by Li-ray spectroscopy. The detection results are as follows: Figure 4 As shown.

[0092] The ionic conductivity of the electrolytes or electrolyte solutions prepared in Examples 1, 3, and 4 of this invention was detected by electrochemical impedance spectroscopy. The detection results are as follows: Figure 5 As shown.

[0093] The Bruce-Vincent method was used to apply a polarization voltage to lithium-lithium symmetric batteries, and the lithium ion transport numbers in the electrolytes or solutions prepared in Examples 1-3, Comparative Examples 1, and Comparative Examples 3-5 of this invention were detected. The detection results are as follows: Figure 6 As shown.

[0094] Depend on Figure 3 It can be seen that, compared with the electrolyte prepared in Comparative Example 1, the electrolytes prepared in Comparative Example 3 and Example 1 contain... 7 The full width at half maximum (FWHM) of the Li signal significantly increased, indicating that after polymerization and solidification, the degree of freedom of electrolyte molecules decreased, and the chemical environment of lithium ions became more complex. Further comparison of chemical shifts revealed that, in Comparative Example 3… 7 The Li signal shifts significantly towards the lower field (Δδ = 0.052 ppm) because the ether group on the tri(ethylene glycol) diacrylate monomer coordinates with lithium ions through strong ion-dipole interactions. In contrast, the signal in Example 1... 7 The Li signal only shifts slightly to the lower field (Δδ=0.019ppm), which indicates that the fluorinated cyclotriphosphazene crosslinking agent containing double bonds and the fluorinated acrylate monomer selected in this invention have a weak coordination ability for lithium ions after full crosslinking and polymerization, and the three-dimensional network framework hardly affects the original solvation structure of lithium ions.

[0095] Depend on Figure 4 It can be seen that the electrolyte prepared in Comparative Example 1 has the highest lithium-ion relaxation rate, which is 1.13 s. -1 Compared to Comparative Example 1, the relaxation rate of lithium ions in the electrolytes prepared in Comparative Example 3 and Example 1 decreased, but with the increase of monomer feed in their respective systems, they showed different trends.

[0096] Specifically, when the amount of pentaerythritol tetraacrylate added is fixed at 2 wt% of the base electrolyte mass, when the amount of tri(ethylene glycol) diacrylate added is increased from 2 wt% to 4 wt% and 6 wt% (both relative to the base electrolyte mass) and both are fully cross-linked and polymerized, the relaxation rate of lithium ions in the electrolyte produced by this system increases from 0.85 s⁻¹. -1 It decreased sequentially to 0.78s. -1 0.70s-1 The concentration of lithium ions in the polymer system continues to decline. This is because the ether group in tri(ethylene glycol) diacrylate has a strong lithium ion coordination ability. As the monomer feed increases, the content of ether group in the polymer system increases accordingly, and its coordination effect on lithium ions continues to accumulate, thereby significantly reducing the mobility of lithium ions.

[0097] In contrast, when the amount of the fluorinated acrylate-cyclotriphosphazene crosslinking agent shown in Formula 1 is fixed at 2 wt% of the base electrolyte mass, and the amount of fluorinated acrylate is increased from 2 wt% to 4 wt% and 6 wt% (both relative to the base electrolyte mass) and fully crosslinked and polymerized in both cases, the relaxation rate of lithium ions in the electrolyte produced by this system remains basically stable at 1.05 s⁻¹. -1 1.04s -1 and 1.02s -1 This is because the coordination effect between fluorinated acrylates and lithium ions is relatively weak. Especially when using fluorinated acrylate monomers with high functionality, even if the amount of monomer added is increased, it will not significantly inhibit the movement of lithium ions, thus ensuring that the lithium ion movement rate in the highly cross-linked polymer electrolyte remains at a high level.

[0098] Depend on Figure 5 It can be seen that within the temperature range of -20 to 60℃, the ionic conductivity of the electrolytes or electrolyte solutions prepared in Comparative Example 1, Comparative Example 3, and Example 1 all increased with increasing temperature. Among them, the electrolyte solution prepared in Comparative Example 1 exhibited the highest ionic conductivity, followed by the electrolyte prepared in Example 1, and the electrolyte prepared in Comparative Example 3 had the lowest. This ranking is consistent with the detection results of lithium-ion relaxation rate. Taking 20℃ as an example, the ionic conductivity of the electrolyte solution prepared in Comparative Example 1 was 3.32 mS / cm, the ionic conductivity of the electrolyte prepared in Example 1 was 2.74 mS / cm, and the ionic conductivity of the electrolyte prepared in Comparative Example 3 was 1.64 mS / cm. This indicates that polymer skeletons with weak coordination characteristics are more conducive to maintaining the original rapid "onboard" transport mechanism of lithium ions in the basic electrolyte than polymer skeletons with strong coordination characteristics.

[0099] Depend on Figure 6 It can be seen that the lithium-ion transference number of the electrolyte prepared in Comparative Example 1 is 0.49. Compared with Comparative Example 1, the lithium-ion transference numbers of the electrolytes prepared in Comparative Example 3 and Example 1 are both improved. However, as the amount of monomers added in their respective systems increases, the two show different trends.

[0100] Specifically, when the amount of pentaerythritol tetraacrylate added is fixed at 2 wt% of the base electrolyte mass, and the amount of tri(ethylene glycol) diacrylate added is increased from 2 wt% to 4 wt% and 6 wt% (both relative to the base electrolyte mass) and fully crosslinked and polymerized in both cases, the lithium-ion transference number in the electrolyte produced by this system decreases from 0.61 to 0.56 and 0.52 respectively, showing a continuous downward trend. In contrast, when the amount of fluorinated acrylate-cyclotriphosphazene crosslinking agent shown in Formula 1 is fixed at 2 wt% of the base electrolyte mass, and the amount of fluorinated acrylate added is increased from 2 wt% to 4 wt% and 6 wt% (both relative to the base electrolyte mass) and fully crosslinked and polymerized in both cases, the lithium-ion transference number in the electrolyte produced by this system remains basically stable at 0.68, 0.68, and 0.69 respectively. The aforementioned trend in lithium-ion transference number is consistent with the test results of lithium-ion relaxation rate. The two corroborate each other, jointly indicating that the three-dimensional network framework of the present invention does not contain ether oxygen groups. Even when using high-functionality crosslinking agent II and high-functionality fluorinated acrylate monomers, increasing the amount of feed will not significantly inhibit the movement of lithium ions, thereby ensuring that the lithium-ion movement rate in the highly crosslinked polymer electrolyte remains at a high level.

[0101] The above results collectively demonstrate that by selecting fluorinated acrylate monomers with weak coordination characteristics to construct the polymer skeleton, the present invention imparts good physical morphology and thermal stability to the electrolyte while maximally preserving the intrinsic transport characteristics of lithium ions in the basic electrolyte, thereby taking into account both the structural stability and electrochemical performance of the gel electrolyte.

[0102] (4) An 8.8 Ah lithium metal pouch cell was assembled using the highly cross-linked, low-friction gel polymer electrolyte prepared in Example 1 of this invention, and a long-cycle test was conducted. The test results are as follows: Figure 7 As shown.

[0103] Battery assembly method: A positive electrode sheet is prepared using NCM955 as the positive electrode active material, with a positive electrode active material loading of 22 mg / cm³. 2 Lithium metal was used as the negative electrode, symmetrically arranged on both sides of the positive electrode, with a single-sided negative electrode thickness of 15 μm. Cell stacking was performed in a dry room with a dew point temperature below -50°C. The precursor solution prepared in Example 1 was injected into the cell and allowed to stand at 30°C for 12 hours to allow the electrolyte to fully wet the electrode. Subsequently, thermal polymerization was carried out at 70°C for 0.5 hours, and finally, electrochemical performance testing was conducted.

[0104] Long-cycle testing method: First, activate the battery at a rate of 0.05C for one cycle, then activate the battery at a rate of 0.1C for one cycle; then charge at a rate of 0.2C and discharge at a rate of 0.5C to perform a long-cycle test on the battery, with the cutoff voltage set to 2.8~4.35V.

[0105] Depend on Figure 7 It can be seen that the highly cross-linked, low-friction gel polymer electrolyte prepared in Example 1 of the present invention has excellent interfacial compatibility with the high-nickel layered oxide positive electrode and the highly active lithium metal negative electrode. The large-capacity lithium metal pouch battery assembled using this electrolyte can achieve an ultra-high energy density of 605Wh / kg. After 100 charge-discharge cycles, its capacity retention rate is still maintained at 93%, indicating that the battery system has excellent cycle stability.

[0106] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the claims, or equivalent forms of such scope and boundaries.

Claims

1. A highly cross-linked, low-friction gel polymer electrolyte, characterized in that, include: A three-dimensional network framework formed by polymerization of a fluorinated cyclotriphosphazene crosslinking agent containing double bonds and a fluorinated acrylate monomer, and a basic electrolyte; wherein: the fluorinated cyclotriphosphazene crosslinking agent containing double bonds accounts for 0.5wt%~20wt% of the mass of the electrolyte, the fluorinated acrylate monomer accounts for 0.5wt%~30wt% of the mass of the electrolyte, and the concentration of lithium salt in the basic electrolyte is 0.5mol / L~5mol / L; The fluorinated cyclotriphosphazene crosslinking agent containing double bonds includes any one or more of fluorinated acrylate-cyclotriphosphazene and fluorinated methacrylate-cyclotriphosphazene; The fluorinated acrylate-cyclotriphosphazene group includes a fluorinated acrylate group and a cyclotriphosphazene group, wherein the fluorinated acrylate group includes an acryloxy group and a fluorinated alkoxy group, wherein the oxygen atom in the acryloxy group is bonded to the carbon atom in the fluorinated alkoxy group, and the oxygen atom in the fluorinated alkoxy group is bonded to the phosphorus atom in the cyclotriphosphazene group. The fluorinated methacrylate-cyclotriphosphazene group comprises fluorinated methacrylate group and cyclotriphosphazene group, wherein the fluorinated methacrylate group comprises methacryloxy group and fluorinated alkoxy group, wherein the oxygen atom in the methacryloxy group is bonded to the carbon atom in the fluorinated alkoxy group, and the oxygen atom in the fluorinated alkoxy group is bonded to the phosphorus atom in the cyclotriphosphazene group. The fluorinated acrylate monomers include any one or more of 2,2,2-trifluoroethyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecylfluoroheptyl acrylate, and 2,2,3,3,4,4,5,5-octafluorohexane-1,6-hexanediol diacrylate.

2. The highly cross-linked, low-friction gel polymer electrolyte according to claim 1, characterized in that, The lithium salt includes any one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, and lithium difluorooxalate borate.

3. The highly cross-linked, low-friction gel polymer electrolyte according to claim 1, characterized in that, The basic electrolyte contains a non-aqueous solvent, which includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether.

4. The highly cross-linked, low-friction gel polymer electrolyte according to claim 1, characterized in that, The base electrolyte contains a diluent, which includes one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,1,3,3-pentafluorobutane.

5. A method for preparing the highly cross-linked, low-friction gel polymer electrolyte according to any one of claims 1-4, characterized in that, The process includes the following steps: mixing a fluorinated cyclotriphosphazene crosslinking agent containing double bonds, a fluorinated acrylate monomer, a basic electrolyte, and an initiator in a predetermined ratio, and then carrying out a polymerization reaction at a predetermined temperature to obtain a highly crosslinked, low-friction gel polymer electrolyte.

6. The method for a highly cross-linked, low-friction gel polymer electrolyte according to claim 5, characterized in that, The polymerization reaction is carried out at a temperature of 35~70℃ for a time of 0.5h~12h.

7. The method for a highly cross-linked, low-friction gel polymer electrolyte according to claim 5, characterized in that, The initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.

8. A lithium battery, characterized in that, The lithium battery contains the highly cross-linked, low-friction gel polymer electrolyte as described in any one of claims 1-4.

Citation Information

Patent Citations

  • Cyclotriphosphazene-based flame-retardant polymer electrolyte as well as preparation method and application thereof

    CN115084646A

  • Polymer gel electrolyte, preparation method and application

    CN121439903A